2008
DOI: 10.1525/mp.2008.26.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Styles of Music Listening

Abstract: distinguishes two general cognitive styles. Empathizing is characterized as the capacity to respond to feeling states of other individuals, whereas systemizing is characterized as the capacity to respond to regularities of objects and events. To investigate these traits within the music domain, a questionnaire study (N = 442) was conducted. Construct validity and reliability of the measurement instrument were assessed by factor analysis procedures. A simplified unit weighting (SUW) scale was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
123
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(140 citation statements)
references
References 29 publications
12
123
2
Order By: Relevance
“…ChamorroPremuzic and Furnham (2007) also found that intellectually engaged individuals with higher IQs tended to use music in a different way to neurotic, introverted and non-conscientious individuals. Other studies have discussed gender related differences in response to music (Kreutz et al, 2008, Altenmueller et al, 2002. In relation to sad music, our earlier research (Garrido and Schubert, 2011) discovered significant correlations between absorption, "music empathy," and a liking of sad music.…”
Section: Individual Differences Perspectivementioning
confidence: 80%
“…ChamorroPremuzic and Furnham (2007) also found that intellectually engaged individuals with higher IQs tended to use music in a different way to neurotic, introverted and non-conscientious individuals. Other studies have discussed gender related differences in response to music (Kreutz et al, 2008, Altenmueller et al, 2002. In relation to sad music, our earlier research (Garrido and Schubert, 2011) discovered significant correlations between absorption, "music empathy," and a liking of sad music.…”
Section: Individual Differences Perspectivementioning
confidence: 80%
“…Despite their limitations, self-reports can capture an individual's perception of how they perceive and respond to various types of emotion in music (for example, physiological responses such as getting chills or gooseflesh, feelings of awe or amazement, experiencing strong emotions in response to particular types of music). The Music Empathizing and Music Systemizing scales (Kreutz, Schubert, & Mitchell, 2008), for example, capture the inclination towards empathizing (understanding and responding to affective states of others) or systemizing (understanding characteristics of events and objects). These scales differentiate the tendency to attend to different aspects of music and are helpful for studying differences in cognitive styles of musical processing.…”
Section: Musicianship and Music Capacitymentioning
confidence: 99%
“…Moreover, this approach appears to be favored by participants with an associative DAS (see Table 3). Kreutz et al (2008) concluded that music processing depends on individual cognitive style as well as situational factors. Specifically, cognitive style orients listeners' attention to particular elements of music, such as perceived emotion or musical form.…”
Section: Perceived Exertionmentioning
confidence: 99%
“…An important factor in the study of the effects of music during exercise is that the musical experience is highly individual (see e.g., Priest & Karageorghis, 2008). Cognitive styles have been shown to affect the perception of an external stimulus such as music by focusing attention to the different features and aspects of the stimulus (Kreutz, Schubert, & Mitchell, 2008). Accordingly, DAS may contribute significantly to the variability of the effects of music during exercise.…”
mentioning
confidence: 99%